2004
DOI: 10.1111/j.1365-2362.2004.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Humming‐induced release of nasal nitric oxide for assessment of sinus obstruction in allergic rhinitis: pilot study

Abstract: Absence of a nasal NO peak during humming is associated with endoscopic findings suggestive of sinus ostial obstruction in subjects with allergic rhinitis. Measurement of nasal NO during humming may be a simple method to detect sinus abnormalities in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 36 publications
2
47
2
2
Order By: Relevance
“…This effect was related to the fast gas exchange between sinuses and nose induced by the sounding airflow, which in turn makes sinuses to behave like a kind of Helmholz resonator. Consistently, in both experimental models and in vivo settings, sinus ostium and the natural sinus frequency were the most important factors affecting the great amount of NO released during humming [55,119]. Interestingly, by introducing repeated humming manoeuvres immediately before measurements, NO levels assessed during silent exhalation were reduced, as was the intra-individual variation.…”
Section: Hummingmentioning
confidence: 56%
See 2 more Smart Citations
“…This effect was related to the fast gas exchange between sinuses and nose induced by the sounding airflow, which in turn makes sinuses to behave like a kind of Helmholz resonator. Consistently, in both experimental models and in vivo settings, sinus ostium and the natural sinus frequency were the most important factors affecting the great amount of NO released during humming [55,119]. Interestingly, by introducing repeated humming manoeuvres immediately before measurements, NO levels assessed during silent exhalation were reduced, as was the intra-individual variation.…”
Section: Hummingmentioning
confidence: 56%
“…However, no study reported the prevalence of rhinosinusitis in the studied subjects. Noticeably, in a recent study excluding sinus diseases, allergic rhinitis was associated with higher nasal NO levels, when compared to normal controls [55].…”
Section: Allergic Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies on nasal nitric oxide (nNO) in humans have revealed nitric oxide to be maximally produced from the nasal and paranasal sinus [11][12][13]. There have been also interesting analysis of humming and increased nNO as compared with normal quiet nasal exhalation suggesting improved paranasal sinus ventilation with this maneuver [14,15]. Humming causes the air to oscillate, which in turn seems to increase the exchange of air between the sinuses and the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Since this response is often blunted in pan-sinusitis and/or polyposis, it has been proposed as a non-invasive index of OMC patency, and hence a screening test for severity of rhinosinusitis [28,29]. This maneuver has been well-documented, methodologically, with respect to the effects of sampling mode, humming frequency, and nNO depletion by repeated sampling ("washout") [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%